Multiple Stressors and Ecological Complexity Require a New Approach to Coral Reef Research - Pendleton, Linwood H.; Hoegh-Guldberg, Ove; Langdon, Chris; Comte, Adrien (Frontiers in Marine Science, 2016)
Ocean acidification, climate change, and other environmental stressors threaten coral reef ecosystems and the people who depend upon them. New science reveals that these multiple stressors interact and may affect a multitude of physiological and ecological processes in complex ways. The interaction of multiple stressors and ecological complexity may mean that the negative effects on coral reef ecosystems will happen sooner and be more severe than previously thought. Yet, most research on the effects of global change on coral reefs focus on one or few stressors and pathways or outcomes (e.g. bleaching). Based on a critical review of the literature, we call for a regionally targeted strategy of mesocosm-level research that addresses this complexity and provides more realistic projections about coral reef impacts in the face of global environmental change. We believe similar approaches are needed for other ecosystems that face global environmental change.